Analisis Efektivitas Prosedur Dan Pelaksanaan Penerbitan Lisensi Personel Navigasi Penerbangan Pada Direktorat Navigasi Penerbangan - Suprihatin Suprihatin; Dodi Rahmat Setiawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to determine and analyze conditions, obstacles, and solutions in an effort to increase the effectiveness of the Procedure and Implementation of the Issuance of Aviation Navigation Pesnel Licenses at the Directorate of Aviation Navigation. The concept used in this research is effectiveness. This research was conducted at the Directorate General of State Transportation from February 2021 to June 2021. The informants in this study were 7 people. The result of this research is that the effectiveness of the organization has been well appointed by the examiners, where the characteristic variables, environmental characteristics, employee characteristics, and management practice policies have been running well. The obstacles that exist in the company such as: a) the lack of personnel of examiners; b) uneven improvement of supporting facilities; c) requirements are not met. Efforts are made to overcome the obstacles that can be done: increasing the number of members for equal distribution of tasks; equitable distribution of facilities for supporting activities; take online certification to meet the required requirements.